Effect of Some Environmental Factors on the Properties of Polyurethane/Silica Composites - falih, Hazim (Anbar Journal of Engineering Sciences, 2009)
Silica particles are directly introduced into polyurethane resin with different grain size and different volume fractions to obtain a new composite. Hardness, impact strength (charpy) and compression properties were studied with the conditions mentioned; Acid solutions and UV- radiation were the main environments studied on the samples prepared. The results showed that the acid affected the properties more than UV- radiation